Targeting Interleukin-18 (IL-18) in malaria infection - Basir, Rusliza; Kartini, Hasballah; Ismail, Sabariah; Gam, Lay Harn; Mahmud, Roziahanim; Abdul Majid, Amin Malik (2009)
The potential of IL-18 as drug target during malaria infection was investigated in an experimental model. IL-18 production during the infection was modulated with IL-18 related drugs and the effects on the course of infection and the release of pro- and anti-inflammatory cytokines were evaluated. Malaria infection was initiated by inoculation of mice with Plasmodium berghei parasite. Modulation of IL-18 production was carried out by treatment with recombinant mouse IL-18 binding protein, anti-IL-18 monoclonal antibody or recombinant IL-18. The plasma concentrations of IL-18 and other cytokines were measured by ELISA technique. IL-18 expression in local tissues was determined through western blotting method. The course of infection was monitored throughout the infection and treatment. Plasma IL-18 was significantly elevated and positively correlated with parasitaemia development during the infection. Significant expressions of IL-18 were observed in the spleen, liver and brain tissues of infected mice. Plasma concentrations of pro-inflammatory cytokines (TNF, IL-1, IFN, IL-6) decreased significantly upon inhibition and neutralization of IL-18, whereas the anti-inflammatory cytokine IL-10 increased significantly. Augmenting the production of IL-18 during the infection significantly increased the release of pro-inflammatory cytokines further in the plasma whereas the anti-inflammatory cytokine was reduced. Significant increase in parasitaemia development and earlier mortality were also observed in infected mice when IL-18 release was further augmented. Results suggest the crucial role of IL-18 in malaria infection and targeting IL-18 may prove to be beneficial to the host and IL-18 may potentially be developed as an important immunotherapeutic target for malaria therapy.